Pengaruh gaya hidup, ekuitas merek dan marketing mix terhadap keputusan pembelian di Esteh Indonesia Kota Gorontalo menggunakan metode Structural Equation Modelling - Arya, Muhammad Farza; Rasyid, Abdul; Uloli, Hendra (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The decline in sales of Esteh Indonesia in Gorontalo is caused by healthy lifestyle trends, increased competition, and ineffective marketing strategies. This study evaluates the influence of lifestyle, brand equity, and marketing mix on purchasing decisions using the Structural Equation Modeling method. This descriptive quantitative research used purposive sampling with 324 respondents from a population of 1730 with an error rate of 5%. The data was analyzed using statistical tests and the Strucutral Equation Modeling model. The results show that lifestyle, brand equity, and marketing mix significantly influence the purchasing decisions of Esteh Indonesia consumers in Gorontalo City, with tcount greater than ttable and P-value below 0.05. The conclusion states that these variables, both partially and simultaneously, influence purchasing decisions. Suggestions for Esteh Indonesia management in Gorontalo City are to strengthen brand equity, adapt products to healthy lifestyle trends, and improve more effective marketing strategies.